KITAB KUNING LITERACY THROUGH THE SOROGAN TRADITION: A MODEL FOR STRENGTHENING SANTRI’S RELIGIOUS UNDERSTANDING - Zaky Fajar Taufiqurrahman (Journal Of Islamic Education And Pesantren, 2021)
This study aims to analyze yellow book literacy within the sorogan tradition as a model for strengthening students’ religious understanding at Tebuireng Islamic Boarding School, Jombang. The research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with religious teachers and students, and analysis of the takhasus curriculum documents. Data were analyzed using interactive processes of reduction, display, and verification. The findings reveal that yellow book literacy is not merely a technical skill of reading unvowelled Arabic texts but a structured socio-epistemic practice embedded in the pedagogical system of sorogan. The sorogan tradition functions as an intellectual apprenticeship mechanism that reproduces scholarly authority, shapes religious habitus, and strengthens Islamic understanding in a methodological and argumentative manner. Pesantren social literacy provides the normative framework, while sorogan operationalizes it through dialogical practice, resulting in systematic and reflective intellectual dispositions among students. This study concludes that turats literacy within the sorogan tradition represents an integrative pedagogical model that remains relevant in preserving the epistemic depth of Islamic education amid modernization challenges.